Efektivitas Program Parenting Di Pusat Pembelajaran Keluarga (Puspaga): Studi Kasus di Dinas Pemberdayaan Perempuan Perlindungan Anak Pengendalian Penduduk Dan Keluarga Berencana Kota Surabaya - Ahmad Bayu Dwi Rahman; Kendry Widiyanto (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2023)
This study aims to find out that the PUSPAGA Parenting Program is successful in increasing parents' knowledge about important aspects of child development, such as education, health care, psychological aspects, and stages of child development. Parents who join the program also tend to be more involved in their children's educational and developmental lives, support them in their learning, and be active in the educational process. In addition, the program helps parents to develop more effective parenting patterns with a better understanding in dealing with daily challenges. This research uses a qualitative method with the type of approach used is a descriptive approach. The data collection methods used were interviews, documentation, and literature studies of previous research. The PUSPAGA parenting program has been successful in helping parents improve their ability to care for and educate their children. The results of this study illustrate the effectiveness of the program in providing significant benefits to families and child development. Such parenting programs have a crucial role in improving the quality of family life and ensuring optimal child development according to their potential.